2023
DOI: 10.30862/jri.v3i1.213
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the factors influencing the attitudes of students toward the study of mathematics

Abstract: The purpose of the study was to investigate the factors influencing the attitude of students towards the study of mathematics in selected Junior High Schools in Asokore in the Sekyere East District of the Ashanti Region of Ghana. The study was based on the ABC Attitude Model. Random sampling was used to select 102 respondents (students) in Asokore in the Sekyere East District for the study. A questionnaire was the sole instrument employed in the study. Descriptive statistics were used to analyze the data. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition, the results of student interviews revealed that the lack of accessible resources, such as books and modules, made it difficult for students to learn fundamental mathematical ideas. To motivate students to learn mathematics, creativity is required (Amoah et al, 2023;Matorevhu, 2023). This research aims to develop an interactive emodule based on the case method to improve students' HOTs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results of student interviews revealed that the lack of accessible resources, such as books and modules, made it difficult for students to learn fundamental mathematical ideas. To motivate students to learn mathematics, creativity is required (Amoah et al, 2023;Matorevhu, 2023). This research aims to develop an interactive emodule based on the case method to improve students' HOTs.…”
Section: Introductionmentioning
confidence: 99%